Evaluation of hypolipidemic effect of Pueraria tuberosa extract on high-fat diet induced hyperlipidemia in Wistar rats - Kumaresan, Vinoodh Kumar; Joshi, Shirish S.; Shetty, Yashashri C.; Doke, Madhuri Tanaji (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Low-density lipoproteins (LDL)-C plays a pivotal role in the development of atherosclerosis, and its reduction is a primary target in the management of dyslipidemia. Pueraria tuberosa contains Puerarin, increases LDL receptor (LDLr) mRNA and HMG-CoA reductase mRNA invitro. However, its role as an hypolipidemic agents needs further elucidation. Methods: IAEC permission was sought (IAEC/GSMC/05/2022). Wistar rats of either sex around 150-200 grams were divided into 5 groups (n= 8). Group NC (Normal control) received a normal chow diet while Group DC (disease control), Group PC (Atorvastatin 10mg/kg/day), Group PTE LD (PTE 500mg/kg/day) and Group PTE HD (PTE 1000mg/kg/day) received high-fat diet for 45 days. Atorvastatin and Pueraria tuberosa aqueous extract (PTE) were given from the 15th day to the 45th day to the respective groups. Lipid profile, and HMG COA reductase enzyme levels were analysed and compared between groups using one-way ANOVA and Kruskal-Wallis test followed by post hoc analysis (p<0.05). Results: PTE HD significantly decreased total cholesterol and LDL-C, compared to the disease control group. Conclusions: According to our findings, Pueraria tuberosa aqueous extract exert a hypolipdemic effect at higher doses as evidenced by decrease in total cholesterol and LDL-C.